c-Myb regulates matrix metalloproteinases 1/9, and cathepsin D: implications for matrix-dependent breast cancer cell invasion and metastasis - Knopfová, Lucia; Beneš, Petr; Pekarčíková, Lucie; Hermanová, Markéta; Masařík, Michal; Pernicová, Zuzana; Souček, Karel; Smarda, Jan (Molecular cancer, 2012)
BACKGROUND: The c-Myb transcription factor is essential for the maintenance of stem-progenitor cells in bone marrow, colon epithelia, and neurogenic niches. c-Myb malfunction contributes to several types of malignancies including breast cancer. However, the function of c-Myb in the metastatic spread of breast tumors remains unexplored. In this study, we report a novel role of c-Myb in the control of specific proteases that regulate the matrix-dependent invasion of breast cancer cells. RESULTS: Ectopically expressed c-Myb enhanced migration and ability of human MDA-MB-231 and mouse 4T1 mammary cancer cells to invade Matrigel but not the collagen I matrix in vitro. c-Myb strongly increased the expression/activity of cathepsin D and matrix metalloproteinase (MMP) 9 and significantly downregulated MMP1. The gene coding for cathepsin D was suggested as the c-Myb-responsive gene and downstream effector of the migration-promoting function of c-Myb. Finally, we demonstrated that c-Myb delayed the growth of mammary tumors in BALB/c mice and affected the metastatic potential of breast cancer cells in an organ-specific manner. CONCLUSIONS: This study identified c-Myb as a matrix-dependent regulator of invasive behavior of breast cancer cells.
Keywords: Animals; Electrophoresis, Polyacrylamide Gel; metastázy nádorů; Proto-Oncogene Proteins c-myb; nádory prsu; Female; Cell Line, Tumor; ženské pohlaví; Matrix Metalloproteinase 1; protoonkogenní proteiny c-myb; matrixová metaloproteinasa 1; lidé; Mice; Breast Neoplasms; malá interferující RNA; Mice, Inbred BALB C; Matrix Metalloproteinase 9; myši; Immunoblotting; pohyb buněk; matrixová metaloproteinasa 9; Cathepsin D; myši inbrední BALB C; RNA, Small Interfering; kathepsin D; imunoblotting; Cell Movement; zvířata; Neoplasm Metastasis; elektroforéza v polyakrylamidovém gelu; kvantitativní polymerázová řetězová reakce; nádorové buněčné linie; Real-Time Polymerase Chain Reaction; Humans